Learning Webs for Doctrinal Education (Pariyatti Dhamma) of Buddhist Monks in Contemporary Thai Monastic Society: A Policy Recommendation - Yanakitti, Phramaha Warantorn; Raksachom , Maechee Kritsana; Kraichakr, Orachon; Thongoran , Charatluck (Mahachula Academic Journal, 2026)
This academic article aims to propose policy recommendations on Learning Webs for Buddhist scriptural education (Phra Pariyatti Dhamma) for monks in contemporary Thai society, based on the concept of Ivan Illich. The study employs a documentary research approach, examining relevant literature on the management of Buddhist scriptural education in the current Thai monastic community, as well as the concept of Learning Webs as proposed by Ivan Illich. Based on this analysis, policy recommendations on Learning Webs for Buddhist scriptural education for monks in contemporary Thai society are formulated. The findings reveal that the proposed policy on Learning Webs for Buddhist scriptural education for monks in contemporary Thai society, grounded in Ivan Illich’s concept, consists of four key operational approaches:(1) Provision of Learning Resources for Buddhist Scriptural Education: This involves developing digital platforms as centralized databases of learning resources and establishing collaborative networks with educational institutions. Such efforts aim to enable monks to access Buddhist knowledge conveniently, efficiently, and equitably.(2) Learning with Expert Monks: This includes the selection of highly knowledgeable monks in various fields, the development of digital platforms to create databases of expert monks, and the promotion of both individual and large-group learning in online formats. This approach ensures equitable access to expertise and educational opportunities. (3) Peer Matching for Collaborative Learning: This involves the development of digital platforms to match monks with shared learning interests, as well as the creation of interactive spaces for continuous knowledge exchange and collaborative learning.(4) Professional Buddhist Educators: This entails the selection and appointment of professional monk educators, along with the establishment of structured systems for managing Buddhist scriptural education and providing academic advising. These mechanisms are designed to systematically and continuously support, promote, and plan monks’ learning processes.